El Mercurio and Labor Press: Two journalistic approaches for building a Nation - Rivas Inostroza, Fernando (2013)
The media helps to symbolically build the nation by its effect, mainly on culture and, through it, on the different sides and areas of the citizens’ activities. However, the means vary. Here we review and compare what was done by El Mercurio de Santiago with its first and canonic editorial in 1900, to what was done by another canonical publication, this time a Chilean labor press. The latter was written by one of the dignitaries of the Chilean syndicalism, Luis Emilio Recabarren.